2020
DOI: 10.1021/acs.energyfuels.0c01903
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Matrix Swelling and Its Effects on Fracture Structure and Permeability for a High-Rank Coal Based on X-ray Micro-CT Image Processing Techniques

Abstract: The adsorption gas of coal matrix will cause its swelling, change the fracture structure, and further affect the permeability of the coal seam. In this study, CT image processing technology was used to numerically simulate the swelling of different extents (0.05%, 0.10%, 0.15%, 0.20%, and 0.25%). At the same time, the evolutions of geometric parameters, connectivity, and fractal dimension of fractures under different swelling extents were quantified. The results show that with the increase of the swelling exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Absolute permeability can be defined as the measure of the ability of a porous material to transmit a single phase fluid. , The Stokes equations can be solved for numerically estimating the absolute permeability, , as can be seen in formula : true{ lefttrue · true⃗ V⃗ = 0 μ 2 V⃗ ∇⃗ P = 0 Where · is the divergence operator; is the gradient operator; V is the velocity of the fluid in the fluid phase of the material; μ is still the dynamic viscosity of the flowing fluid; ∇ 2 is the Laplacian operator; and P is the pressure of the fluid in the fluid phase of the material.…”
Section: Samples and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Absolute permeability can be defined as the measure of the ability of a porous material to transmit a single phase fluid. , The Stokes equations can be solved for numerically estimating the absolute permeability, , as can be seen in formula : true{ lefttrue · true⃗ V⃗ = 0 μ 2 V⃗ ∇⃗ P = 0 Where · is the divergence operator; is the gradient operator; V is the velocity of the fluid in the fluid phase of the material; μ is still the dynamic viscosity of the flowing fluid; ∇ 2 is the Laplacian operator; and P is the pressure of the fluid in the fluid phase of the material.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Absolute permeability can be defined as the measure of the ability of a porous material to transmit a single phase fluid. 31,32 The Stokes equations can be solved for numerically estimating the absolute permeability, 33,34 as can be seen in formula 4:…”
Section: Calculation Model and Boundary Conditionmentioning
confidence: 99%
“…In the 3D reconstruction of the coal microstructure, the specific grayscale ranges of pore fractures, minerals, and matrix normally determined by threshold segmentation. , As an important basis for 3D reconstruction, the accuracy of threshold determines the accuracy of the final 3D reconstruction model, and the existence of noise in the image makes deviation from the real image inevitable . Therefore, the CT images usually require further processing, including adjusting the image contrast and filtering the scatter dots noise prior to segmentation. Using the preprocessed three-dimensional (3D) image, the threshold segmentation is calibrated along with measured porosity (MIP or other methods), and then used to obtain the 3D coal microstructure (see Figure ). ,, …”
Section: Quantitative Characterization Of Microstructurementioning
confidence: 99%
“…Adsorption time, adsorption pressure, and the microstructure affect the swelling deformation of the coal matrix after gas adsorption, and the changes in the porosity and permeability of coal after adsorption are closely related to the gas pressure in the pores and fractures and the degree of coal matrix swelling deformation. By evaluating the internal microstructure of coal under different adsorption pressures using CT and simulating coal swelling deformation using the Avizo software, the results showed that, as the adsorption pressure of gas increases, the thickness of typical fractures in the coal decreases significantly (see Figure ), causing a negative exponential decrease in porosity and permeability. , The preswelling stage of the coal matrix shows a significant decrease in fracture length, followed by a substantial decrease in fracture width …”
Section: Dynamic Evolution Of Microstructure and Macroscopic Properti...mentioning
confidence: 99%
See 1 more Smart Citation